Monitoring and evaluation of policy influence and advocacy - and Tsui, Josephine; Hearn, Simon; Young, John (ODI, 2014)
Policy influence and advocacy are increasingly regarded as a means of creating sustainable policy change in international development. It is often also seen as a difficult area to monitor and evaluate. Yet there is an increasingly rich strand of innovation in options to monitor, evaluate and learn from both the successes and failures of policy influence and advocacy interventions. This paper explores current trends in monitoring and evaluating policy influence and advocacy; discusses different theories of how policy influence happens; and presents a number of options to monitor and evaluate different aspects of advocacy interventions. Case studies describe how some organisations have used these options in practice to understand their impact and improve their advocacy strategies.